Chemical amplification accelerates reactive oxygen species triggered polymeric degradation. (28th November 2017) - Lee, Sangeun; Stubelius, Alexandra; Olejniczak, Jason; Jang, Hongje; Huu, Viet Anh Nguyen; Almutairi, Adah
Abstract : Chemical amplification strategy is employed to accelerate degradation of ROS-responsive polymeric nanoparticles. Abstract : Chemical amplification is a known strategy for improving the sensitivity of stimuli-responsive polymers. However, the chemical amplification effect has never been fully examined. Many questions remain about its mechanism and efficacy, obstructing its further implementation. Here, we design and demonstrate a reactive oxygen species (ROS) responsive polymer (ROS-ARP) with a chemical amplification strategy to dismiss these concerns. The ROS-ARP is designed to change the hydrophilicity by ROS, revealing a carboxylic acid, which also catalyzes ketal hydrolysis along the polymer backbone. The chemical amplification strategy of ROS-ARP accelerated the polymer degradation up to 17 fold compared to a previously reported ROS-responsive polymer. To investigate the mechanism behind this increased acceleration, we compared the degradation kinetics in various environments. Additionally, other effects such as hydrophilicity changes were excluded. The accelerated degradation of ROS-ARP is evaluated as a potential drug delivery system, demonstrating on-demand cargo release from the formulated polymeric particles.